2019
DOI: 10.1177/1179573519843880
|View full text |Cite
|
Sign up to set email alerts
|

Linear Accelerator-Based Stereotactic Radiotherapy for Low-Grade Meningiomas: Improved Local Control With Hypofractionation

Abstract: Background and purpose: Meningioma is a common type of benign tumor that can be managed in several ways, ranging from close observation, surgical resection, and various types of radiation. We present here results from a 10-year experience treating meningiomas with a hypofractionated approach. Materials and methods: We reviewed the charts of 56 patients treated with stereotactic radiosurgery (SRS) or hypofractionated stereotactic radiotherapy (SRT) from 2008 to 2017. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
4
5
0
Order By: Relevance
“…Due to the lack of studies with large patient numbers, statistics for OS and LC in WHO grade II and III meningiomas show a broad variance (0.0-89.0%) (Table 3) [30,32,33,38,40,42,43]. Our estimated 5-year LC for WHO grade II (66.7%) and WHO grade III (53.1%) meningiomas is compatible with the majority of published data (Table 3) [11,13,15,30,32,33,38,40,42,[44][45][46][47]. Our 5-year and 10-year OS rates for each WHO grade, however, seem to be more favorable in comparison to published ones.…”
Section: Discussionsupporting
confidence: 87%
“…Due to the lack of studies with large patient numbers, statistics for OS and LC in WHO grade II and III meningiomas show a broad variance (0.0-89.0%) (Table 3) [30,32,33,38,40,42,43]. Our estimated 5-year LC for WHO grade II (66.7%) and WHO grade III (53.1%) meningiomas is compatible with the majority of published data (Table 3) [11,13,15,30,32,33,38,40,42,[44][45][46][47]. Our 5-year and 10-year OS rates for each WHO grade, however, seem to be more favorable in comparison to published ones.…”
Section: Discussionsupporting
confidence: 87%
“… 18 Publications of hypofractionated regimens have reported similar rates of control (>90%), but with a limited range of tumor volumes (<75 cm 3 ). 4 , 11 , 19 , 20 , 21 , 22 , 23 , 24 In the context of these studies, our findings support a similar efficacy of moderately hypofractionated radiation for larger tumor volumes (up to 245 cm 3 ) and those near critical structures.…”
Section: Discussionsupporting
confidence: 79%
“…One prior study has shown statistically significant association between development of post-treatment peritumoral edema and single-fraction SRS versus hypofractionated SRS courses [ 15 ]. In addition, hypofractionated SRS is preferred over SRS for tumors larger than 10 cm 3 and multiple studies have shown excellent outcomes with low toxicity (less than 5%) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%